Insomnia symptoms, objective sleep duration and hypothalamic‐pituitary‐adrenal activity in children. (May 2014) - Fernandez‐Mendoza, Julio; Vgontzas, Alexandros N.; Calhoun, Susan L.; Vgontzas, Angeliki; Tsaoussoglou, Marina; Gaines, Jordan; Liao, Duanping; Chrousos, George P.; Bixler, Edward O.
Abstract Background Insomnia symptoms are the most common parent‐reported sleep complaints in children; however, little is known about the pathophysiology of childhood insomnia symptoms, including their association with hypothalamic‐pituitary‐adrenal (HPA) axis activation. The objective of this study is to examine the association between parent‐reported insomnia symptoms, objective short sleep duration and cortisol levels in a population‐based sample of school‐aged children. Design A sample of 327 children from the Penn State Child Cohort (5–12 years old) underwent 9‐h overnight polysomnography and provided evening and morning saliva samples to assay for cortisol. Objective short sleep duration was defined based on the median total sleep time (i.e., < 7·7 h). Parent‐reported insomnia symptoms of difficulty initiating and/or maintaining sleep were ascertained with the Pediatric Behavior Scale. Results Children with parent‐reported insomnia symptoms and objective short sleep duration showed significantly increased evening (0·33 ± 0·03 μg/dL) and morning (1·38 ± 0·08 μg/dL) cortisol levels. In contrast, children with parent‐reported insomnia symptoms and 'normal' sleep duration showed similar evening and morning cortisol levels (0·23 ± 0·03 μg/dL and 1·13 ± 0·08 μg/dL) compared with controls with 'normal' (0·28 ± 0·02 μg/dL and 1·10 ± 0·04 μg/dL) or short (0·28 ± 0·02 μg/dL and 1·13 ± 0·04 μg/dL) sleep duration. Conclusions Our findings suggest that insomnia symptoms with short sleep duration in children may be related to 24‐h basal or responsive physiological hyperarousal. Future studies should explore the association of insomnia symptoms with short sleep duration with physical and mental health morbidity.